Motivation and its Impact on Teachers’ Productivity in Secondary Schools in Njokoka L. G. A. of Anambra State, Nigeria - OGBUDINKPA, Ijeoma Charity (International Journal of Educational Management, 2021)
This research is carried out to study the impact of motivation on teacher’s local government in secondary schools in Njikoka Local Government Area of Anambra State. Simple random sampling technique was used to select 10 out of thirteen schools. Questionnaires were designed for data collection. The one questionnaire on teachers productivity scale (TPS) were administered to rate job productivity of teachers. Pearson Product Moment Correlation was used to find out the impact of motivation on teachers job productivity in secondary schools in Njikoka Local Government Area of Anambra State. The findings of the study indicated that the motivation variables were found to be related significantly to the productivity of teachers. Based on the findings it was recommended that educational administrations should pay high attention to teacher’s welfare, prompt pay method, encouragement and promotion as well as involvement of teachers in the school administration for effective decision making process.